NLRC4 Mutation in flagellin-derived peptide CBLB502 ligand-binding domain reduces the inflammatory response but not radioprotective activity. (10th October 2019) - Lai, Lili; Yang, Ganggang; Yao, Xuelian; Wang, Lei; Zhan, Yiqun; Yu, Miao; Yin, Ronghua; Li, Changyan; Yang, Xiaoming; Ge, Changhui
ABSTRACT: Bacterial flagellin is a pathogen-associated molecular pattern recognized by surface-localized Toll-like receptor 5 (TLR5) and cytosolic NOD-like receptor protein 4 (NLRC4). CBLB502, derived from Salmonella flagellin, exhibits high radioprotective efficacy in mice and primates by regulating TLR5 and the nuclear factor kappa B (NF-κB) signaling pathway. In this study, we examined the effects of CBLB502 and mutations in its NLRC4- and TLR5-binding domains on radioprotective efficacy and the immune inflammatory response. The results showed that CBLB502 mutation with I213A in the TLR5-binding domain significantly reduced NF-κB activity and radioprotective activity, whereas CBLB502 mutation with L292A in NLRC4-binding domain did not. Additionally, CBLB502 with both mutations greatly reduced NF-κB activity and eliminated radioprotection in mice. In contrast, NLRC4-binding domain mutation reduced the secretion of inflammatory interleukin-1β and interleukin-18. CBLB502 exerts its radioprotective effects through both the TLR5 and NLRC4 pathways. Additionally, deletion in the NLRC4-binding domain did not reduce radioprotective activity but reduced the inflammatory response.